Pengaruh subtitusi tepung fungsional lokal (TFL) campuran ulat sagu terhadap mutu sensorik dan kadar air biskuit - Nadimin Nadimin; Hijrah Asikin; Apgractia Feroshinta Liding; Andi Humaerah Aldillah (AcTion: Aceh Nutrition Journal, 2022)
Local foodstuffs, including sago worms, contain high nutrients and are widely available in Indonesia, but until now have not been optimally utilized. Through food technology efforts, substituting sago worm into flour is very good for developing local food biscuits. This study aims to analyze the effect of Local Functional Flour (TFL) substitution on biscuits' sensory quality and moisture content. The study used a completely randomized design (CRD) with a one-shot group design. The TFL formulation consisted of sago worm, soybean, mung bean, and carrot. The best biscuits were selected using the weighting method on the sensory aspects of color, texture, aroma, and taste. Statistical analysis used the Kruskal-Wallis test at 95% CI. The results showed that there was no effect of TFL substitution on the sensory quality of biscuits from the aspects of color (p= 0,086), texture (p= 0,818), aroma (p= 0,126), and taste (p= 0,516). Biscuits with the best sensory quality were with 20% local flour substitution. Textural changes occurred in the biscuits during storage using plastic packaging in the second week of storage. The water content of biscuits stored in plastic packaging increased by 2,12 to 2,53%. In conclusion, TFL substitution did not affect the sensory quality of biscuits. Biscuits' sensory quality and water content can be maintained through storage in watertight containers.